Restorative Justice in the Reform of the Indonesian Criminal System (Case Study of Violence Against Children in the Selebar Police Sector Area, Bengkulu City) - Gustika Maharian, Safira (Journal of Law, Politic and Humanities, 2024)
Imprisonment in several criminal cases is considered ineffective. This is because there is no guarantee that when the convict is released, he will be better or worse. The classical school is also considered irrelevant to the modern life of today's society. In dealing with criminal acts that can be restored or restored, a paradigm of punishment is known, namely restorative justice , in which the perpetrator is encouraged to compensate for the losses that have been caused to the victim, his family and also the community. The research method used is normative juridical referring to the approach in legal science. The results of this study are efforts to reform criminal law in the application of restorative justice based on police report number LP / B / 71 / VI / 2023 / SPKT / POLSEK SELEBAR / POLRESTA BENGKULU / POLDA BENGKULU in Indonesia still has shortcomings because there is no law that specifically regulates restorative justice . In the National Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, it only focuses on administrative matters in the police, not on restorative justice itself. The implementation of Restorative Justice in the punishment of perpetrators of criminal acts in Indonesia is very good considering that there is no law that specifically regulates restorative justice itself . In 2022 , the number of cases resolved using the restorative justice system was 15,809 cases . This number increased by 11.8 % compared to the number in 2021 of 14,137 cases.